3D printing and modeling of congenital heart defects: A technical review. Issue 13 (31st July 2018) - Townsend, Kevin; Pietila, Todd
Abstract : Use of 3D printing technology is expanding in healthcare. One of the common applications is the creation of anatomical models of congenital heart defects (CHD) from medical image data. These patient‐specific models are being used for multiple purposes including visualization of anatomy, simulation of surgical procedures, patient education, and facilitating communication between clinical staff. The process for creating CHD models begins with acquiring volumetric image data that is segmented using medical image processing software. A virtual 3D model is calculated based on the segmented data which can be further refined using computer‐aided design software. Last, the virtual model is transferred to a 3D printer for production. By obtaining detailed knowledge on the process for creating patient‐specific CHD anatomical models, institutions can implement the technology in an efficient and cost‐effective manner.